Pseudo-disbelief Allegories in the Works of Ein al-Qozat Hamedani (with Emphasizing on Letters and Arrangements) - Ahmad Amin; Ali Mohammadi Asiabadi; Seyyede kowsar Rohban (مطالعات زبانی و بلاغی)
Since the expression of mystical experiences in the form of a limited and inefficient material language is a very difficult and challenging task, the mystics have used the artistic capacities of the language as a parable to explain and understand their mystical thoughts and experiences and to persuade the audience. Ein al-Qodat Hamedani is one of the mystics who has found this linguistic sense in his works. But it is worth noting that sometimes the judge makes a certain statement of the allegory that, in addition to the apparent level of the word, we are faced with a paradoxical and contradictory structure at the spiritual level. This form of allegorical expression, which brings to mind the structures of Pseudo-disbelief in the language, can be called "Shathi allegories". In this brief, it is intended that this approach and application of allegory in the works of Ein-al-Qozat Hamedani be examined and based on the cluster of images and motifs derived from the particular mystic worldview. Since the frequency of the allegory in the letters and arrangements is more than other works of Ein al-Khedat Hamedani, the two works have been constructed in this study.